A Case Report of Venous Ulcer Mimicking Cutaneous Leishmaniasis - Alaa Tajeldeen Habeeb Abdallah; Emmanuel Edwar Siddig; Jean Claude Semuto Ngabonziza; Claude Mambo Muvunyi; Ayman Ahmed (Clinical Case Reports)
ABSTRACT Venous ulcers can sometimes be difficult to diagnose accurately because they can resemble other skin lesions such as cutaneous leishmaniasis. Here, we present a patient with a venous ulcer that mimics cutaneous leishmaniasis and mycetoma lesions. A 50‐year‐old female patient presented with a nonhealing venous ulcer in her right lower leg, which was suspected to be cutaneous leishmaniasis, ulcerated mycetoma lesions, and misdiagnosed as cutaneous leishmaniasis. She was referred to Rufa'a teaching hospital, Al‐Gezira State, Sudan, where color Doppler sonography results revealed several findings that are consistent with chronic venous insufficiency, including incompetent superficial femoral junction (SFJ) with short reflux among the great saphenous vein (GSV) and incompetent saphenopopliteal junction (SPJ) with short reflux along the small saphenous vein (SSV). Additionally, the examination showed patency and compressibility of both GSV and SSV, as well as the presence of superficial varicose veins. Surgical closure of the fistula was done. This case report highlights the challenges in distinguishing venous ulcers from mycetoma and cutaneous leishmaniasis. The current case emphasizes the importance of considering a comprehensive assessment of the patient's medical history, physical examination, and potentially other diagnostic tests. Collaborating with experienced healthcare providers, such as dermatologists or wound care specialists, may also be beneficial in confirming the diagnosis and developing an appropriate treatment plan.